Salindunong under EDUCator’s CIRcle for Community Linkage and Empowerment Program - Evelyn C. Casareno (International Journal of Scientific Research and Innovative Studies, 2022)
The Salindunong Program aimed to strengthen the execution of quality extension activities to the needy grade school children with the aim of putting premium on their orientation and preparation in handling their technological learning construct in accordance to the demands of education caused by the pandemic. The extension program is a Developmental activity which feature involves the CIPP Model [1] with the following phases: 1.) Needs Assessment, 2.) Program Planning, 3.) Implementation, and 4.) Outcome and Impact. Prior to the execution of the extension program a Memorandum of Understanding (MOU) was established between the Teacher Education Program and Sto. Tomas Elementary School, together with the formal identification of participants and their needs. After a series of implementation, a survey questionnaire was administered to the participants which reveals their demographic profile, their expectations on the program, their reasons for attending the sessions and how they utilize their learnings from the session into their schooling. The program subjected the recipients into hands-on technology related activities of which reveals the challenges of the intervention: Internet accessibility, availability of technological resources (cellular phone/tablet/computer) and intervention from the participant's family to further enhance their capacity.